“By Their Own Efforts”: First Nations Health Policy in Canada, 1940s-1970s - Vorobej, Lucy (University of Waterloo, 2023)
This dissertation explores the early years of Ottawa’s 20th century integration policy with a focus on the impact of settler-colonial power and priorities on First Nations’ access to Canadian health care systems under it. Using critical discourse analysis and the theoretical frameworks of Post-Colonialism and Critical Race Theory to read “along the grain of colonial common sense,” this study explores settler archives to examine the discourses, policies, and practices of settler political and bureaucratic leadership from the 1940s to the 1970s. I argue that Ottawa’s policy of integration, despite settler pronouncements of its break from the past, represented a profound continuity of settler desires for Indigenous erasure and White settler power. As a result, many settler politicians and department officials chose willful blindness to First Nations’ assertions of their Indigenous or treaty rights to health care—deemed to be threats to the status quo. In their place, settler leadership drew on racialized myths of First Nations landlessness and “a primitive unproductive” culture to claim exclusive sovereignty, to “justify” settler incursion, and to offer access to settler health care systems on settler terms. Ultimately, Ottawa’s approach produced a system of profound harm. It left Ottawa’s Indian Health Service unprioritized and underfunded, its mandate unwanted by provincial governments, and its policies the target of resistance from many First Nations individuals and communities. My dissertation joins with a rising number of health care historians who recognize that the history of settler-colonialism and systemic racism is a necessary addition to the history of health care in Canada. Specifically, my research will result in a richer understanding of how racialization continued to impact First Nations access to health care during a political period in Canadian history when overt racial discrimination was no longer sanctioned and details how settler efforts to develop policy in “First Nations best interests” ...